Economic Growth: Welfare Of Non-Civil Servant Families - Rukin Rukin; Achmad Fanani Yunianto (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
This research intended to analyze the economic growth and family welfare. The implications on economic growth and welfare in this framework, it is driven by economic growth. This research was conducted in Surabaya which covered 105 supervisors as respondent. This research by utilizing Regression, the technique was processed with SPSS 20 to analyze hypothesis. The intercorrelations models between these variables in this study revealed that the hypothesis have significant correlation. The result of this research were empirical date of the development of the theoretical of economic science.